Mindetale, den 30te Decbr.1829, over afdøde Geheime-Statsminister Ove Malling. - Zornemann, J. M. (Tidsskrift for Landøkonomi, 2018)
Mindetale, den 30te Decbr.1829, over afdøde Geheime-Statsminister Ove Malling.